Barāha purāṇa - Dāna, Nārāẏaṇa Candra (Dharmagrantha Shṭora, 1970)
Verse abridgement of the Varāhapurāṇa, Hindu mythological text, narrating the story of Varaha, incarnation of Vishnu; based on a palmleaf manuscript of Kāmapāḷa Dāśa.